Bulimia nervosa in obese patients qualified for bariatric surgery – clinical picture, background and treatment - Marzena Sekuła; Iwona Boniecka; Krzysztof Paśnik (Videosurgery and Other Miniinvasive Techniques)
Eating is a basic human physiological need which is necessary to keep the body alive. Eating disorders are diagnosed when eating (or not eating) and associated body weight gain anxiety become the main interest of an individual and all other spheres of life depend on it. Bulimia nervosa is a psychiatric disorder which is more and more commonly diagnosed in patients suffering from obesity and in patients after surgical treatment of obesity. In patients eligible for bariatric surgery this disorder should be diagnosed appropriately early and treated successfully before the procedure, because bulimia nervosa does not regress spontaneously. When untreated, it may last for years, reducing the efficacy of a surgical treatment of obesity, or even lead to complications that are health- and life-threatening for patients.